2009
DOI: 10.1002/cyto.b.20504
|View full text |Cite
|
Sign up to set email alerts
|

When monocytes and platelets compete: The effect of platelet count on the flow cytometric measurement of monocyte CD36

Abstract: Background: Flow cytometric measurement of monocyte surface CD36 is relevant to several conditions including diabetes, cardiovascular disease, lipid disorders, platelet isoimmunization, and susceptibility to P falciparum malaria. CD36 is also strongly expressed on platelets where it is also known as platelet glycoprotein IV.Methods: Whole blood samples, containing identical monocyte concentrations, were adjusted to contain platelets ranging from 20,000/uL to 600,000/uL, were stained with fluorescent-labeled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Peripheral blood, collected in EDTA, was tested within 48 hours of collection. Previous work demonstrated that monocyte ICAM-1 cell-surface levels were stable for 72 hours after sample collection and were unaffected by the platelet concentration in the sample[26]. Prior to beginning the study, serial testing of samples stored as anticoagulated whole blood in EDTA without continuous mixing at local temperatures demonstrated no statistical difference between monocyte ICAM-1 measurements at day 0 (day of phlebotomy) and day 3 of storage.…”
Section: Methodsmentioning
confidence: 92%
“…Peripheral blood, collected in EDTA, was tested within 48 hours of collection. Previous work demonstrated that monocyte ICAM-1 cell-surface levels were stable for 72 hours after sample collection and were unaffected by the platelet concentration in the sample[26]. Prior to beginning the study, serial testing of samples stored as anticoagulated whole blood in EDTA without continuous mixing at local temperatures demonstrated no statistical difference between monocyte ICAM-1 measurements at day 0 (day of phlebotomy) and day 3 of storage.…”
Section: Methodsmentioning
confidence: 92%
“…This approach is limited by the requirement for fresh blood cells, especially for the analysis of CD36 on monocytes. In addition, measurement of CD36 expression on monocytes in whole blood samples is affected by the platelet count . Accordingly, this quantification approach is not easy to standardize.…”
Section: Discussionmentioning
confidence: 99%
“…This variability may be caused by factors including the origin (plasma or serum), handling (preparation, storage) of the blood samples, and by other specific factors such as different mutations. Several studies have demonstrated up regulation of sCD36 in certain diseases …”
Section: Discussionmentioning
confidence: 99%
“…Values for monocyte CD36 MFI were corrected for the effect of platelet count prior to analysis (Dzik et al , 2010). Complete blood counts were determined by Coulter AC*T8 (Coulter Corp, Miami, FL, USA).…”
Section: Methodsmentioning
confidence: 99%